An experimental investigation of wear of glass fibre-epoxy resin and glass fibre-polyester resin composite materials - Pihtili, Hasim (Pergamon-Elsevier Science Ltd, 2009)
In this paper, the effects of resin content on the wear of woven roving glass fibre-epoxy resin and glass fibre-polyester resin composite materials have been examined. Furthermore, composite materials are experimentally investigated under different loads and speeds by using a block-on-shaft wear tester. The influences of two thermosetting resins epoxy and polyester on the wear of glass-woven roving reinforced composites under has been investigated dry conditions. The glass fibre-epoxy resin and the glass fibre-polyester resin composite materials specimens have been tested under different experiment conditions. Tests were conducted for 0.39 and 0.557 m/s speeds, at two different loads of 5 and 10 N. The weight losses were measured after measuring different sliding distances. Wear in the experiments was determined as weight loss. For each experiment, one specimen was used. The amount of wear was measured before the experiment and after the experiment with the apparatus of balance scales with the accuracy of 10(-3) g. Glass fibre-epoxy resin composites generally showed higher strength and minimum wear when compared with glass fibre-polyester resin composites materials. In addition, Scanning electron microscopy (SEM) is used to study the worn surface to verify the results. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Polyester resin; Epoxy resin; Wear; Composite materials; Glass fibres; Woven fabric